Pengaruh penggunaan pembelajaran student facilitator and explaining dan minat terhadap hasil belajar siswa - Witra Alti; Helmi Hasan (JRTI (Jurnal Riset Tindakan Indonesia), 2019)
This research aims to find out: (1) the outcome of the different learning between student taught by using student facilitator and explaining (SFE) and conventional model and learning outcome by looking from learning interest. (2) the influence of interaction between SFE with conventional models. This research is experimental research (quasi-experiment) with an ANOVA 2x2 factorial design. The outcome of research is (1) there is difference of student learning outcome between student taught by SFE with conventional models, (2) the student outcome who has hight interest taught with SFE  hight more than conventional models, (3) the student outcome learning who has low interest taught with SFE  hight more than with conventional models, (4) there are not an in influence of interaction between student taught student SFE with conventional models.